Hot Subdwarf stars in the integrated light of old stellar populations - Pacheco, Thayse Adineia (2024)
Observational evidence indicates that hot Horizontal Branch stars such as Subdwarfs are the most likely candidates to account for the ultraviolet excess of old globular clusters and elliptical galaxies. These hot and evolved components are still missing in most of the libraries used in the synthesis of stellar populations. Due to this, some differences between models based on resolved and integrated light spectral fitting can translate into age differences of up to 50% in low metallicity globular clusters. To address this problem, we first computed a detailed grid of non-LTE fully line-blanketed stellar atmosphere models for hot and moderately cool Horizontal Branch stars. This new library also provides high-resolution spectra and synthetic photometry in the range from 1 000 10 000 Å, covers ten temperatures within 10 000 <= Tef<= 65 000, five surface gravities in the range 4.5 <= log g <= 6.5, two helium abundances matching two extreme helium-rich and helium-poor scenarios, and two limiting metallicity boundaries regarding both solar ([Fe/H] = 0) and Galactic halos ([Fe/H] = -1,5 and [alfa/Fe] = +0,4). Secondly, this library was combined with others in the literature to model the integrated spectra of simple stellar populations based on the color-magnitude diagrams of NGC 2808 and NGC 7089. We propose modifying the CMD-based methodology in literature by directly matching each observed star to a synthetic spectrum in a ten-dimensional color plane, avoiding inaccuracies of current color-Tef relations. This allows us to quantify the impact of Blue and Extreme Horizontal Branches in the integrated flux, which dominates the light in the far ultraviolet. This approach of stellar population synthesis models will help to break the degeneracy between age and Horizontal Branch morphology which is known to affect the integrated light of old stellar populations.